PERANCANGAN LIFESTYLE CENTER DI PONTIANAK - Chandra, Helen Julia; Andi, Uray Fery; Alhamdani, Muhammad Ridha (JMARS: Jurnal Mosaik Arsitektur, 2025)
The lifestyle changes of urban communities in the modern era are shaped by technological advancements, globalization, and the daily use of social media. These factors have created new tendencies in public activities, particularly among Generation Z and millennials, driving greater interest in culinary, fashion, sports, and recreational activities. Such trends demand urban spaces that are not only functional but also capable of offering meaningful social experiences as a new spatial concept in the city. In major Indonesian cities, this demand is addressed through lifestyle centers"”integrated areas combining retail, culinary, recreation, and open public spaces. These facilities emphasize green open areas, pedestrian accessibility, and social interaction, offering a different experience from conventional shopping malls. As a developing city, Pontianak lacks facilities that comprehensively accommodate various lifestyle needs within a single, well-planned area. The Lifestyle Center design in Pontianak aims to fulfill this gap by providing integrated facilities for culinary, recreation, sports, and fashion. The design method applied refers to the five design steps by Snyder & Catanese, which consist of the initiation stage, preparation stage, analysis and synthesis stage, evaluation stage, and implementation stage. The outcome is a Lifestyle Center envisioned as an adaptive, inclusive, and representative urban hub, fostering both functional and experiential qualities that reflect the evolving lifestyle of Pontianak"™s urban community.